Theory and practice: Selected delivery dynamics in discus throwing - Maheras, A. V. (Techniques Magazine, 2024)
In the discuss throwing, the period of time between the landing of the left foot in the front of the ring and the actual release of the discus, is called the delivery phase. During that phase all discus throwers are in double support (both feet on the ground) for the majority of its duration. However, at the moment the discus is released, there are differences among throwers in that some maintain contat with the ground at that moment, with both feet. Several years ago coaches, particularly Europeans, would advocate the maintenance of both feet on the ground at release, (whether a no reversing, or a quasi reversing of a full reversing of the feet technique was employed), an idea that made sense from a biomechanical point of view and was widely adopted. In fact, those days almost all women discus throwers would exclusivley employ the grounded, double support, technique of releasing the discus. In the subsequent years, work carried by Dapena and Anderst (1997), has shed some light on what may be happening during grounded (one or both feet on the ground), or airborne (both feet off the ground) release of the discus. A discussion of the major concepts involved during that exact phase in discus throwing and whether ont or the other method is more advantageous, is presented below. Since, at the moment of the discus release, its velocity is of paramount importance, the examination of velocity itself is central both in the horizontal and the vertical directions.